Modulation of DNA-Induced Damage and Repair Capacity in Humans after Dietary Intervention with Lutein-Enriched Fermented Milk - Herrero-Barbudo, Carmen (Public Library of Science, 2013)
Dietary factors provide protection against several forms of DNA damage. Additionally, consumer demand for natural products favours the development of bioactive food ingredients with health benefits. Lutein is a promising biologically active component in the food industry. The EFSA Panel on Dietetic Products, Nutrition and Allergies considers that protection from oxidative damage may be a beneficial physiological effect but that a cause and effect relationship has not been established. Thus, our aim was to evaluate the safety and potential functional effect of a lutein-enriched milk product using the Comet Assay in order to analyze the baseline, the induced DNA-damage and the repair capacity in the lymphocytes of 10 healthy donors before and after the intake of the mentioned product. Our data suggest that the regular consumption of lutein-enriched fermented milk results in a significant increase in serum lutein levels and this change is associated with an improvement in the resistance of DNA to damage and the capacity of DNA repair in lymphocytes. Our results also support the lack of a genotoxic effect at the doses supplied as well as the absence of interactions and side effects on other nutritional and biochemicals markers.